2012
DOI: 10.1117/1.jbo.17.10.101505
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ouabain on metabolic oxidative state in living cardiomyocytes evaluated by time-resolved spectroscopy of endogenous NAD(P)H fluorescence

Abstract: Abstract. Time-resolved spectrometry of endogenous nicotinamide dinucleotide phosphate [NAD(P)H] fluorescence is a useful method to evaluate metabolic oxidative state in living cells. Ouabain is a well-known pharmaceutical drug used in the treatment of cardiovascular disease, the effects of which on myocardial metabolism were recently demonstrated. Mechanisms implicated in these actions are still poorly understood. We investigate the effect of ouabain on the metabolic oxidative state of living cardiac cells id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 39 publications
(53 reference statements)
4
23
0
Order By: Relevance
“…This reducing condition is characterized by decrease in the cell oxidation levels towards fully reduced state and, consequently, by rise in NAD(P)H fluorescence intensity. In this situation, the resolved fluorescence lifetime of the NAD(P)H in ''bound'' state was found without change or increased (Chorvatova et al, 2013b), and the redox ratio shifted towards more ''free'' NAD(P)H; this was observed both in rat (Chorvatova et al, 2013b), as well as in human (Cheng et al, 2007) cardiomyocytes. Flavin fluorescence remains mostly unchanged, leading to an increased NADH/FAD ratio.…”
Section: Cell Metabolic Signatures By Time-resolved Nad(p)h Fluorescencementioning
confidence: 84%
See 3 more Smart Citations
“…This reducing condition is characterized by decrease in the cell oxidation levels towards fully reduced state and, consequently, by rise in NAD(P)H fluorescence intensity. In this situation, the resolved fluorescence lifetime of the NAD(P)H in ''bound'' state was found without change or increased (Chorvatova et al, 2013b), and the redox ratio shifted towards more ''free'' NAD(P)H; this was observed both in rat (Chorvatova et al, 2013b), as well as in human (Cheng et al, 2007) cardiomyocytes. Flavin fluorescence remains mostly unchanged, leading to an increased NADH/FAD ratio.…”
Section: Cell Metabolic Signatures By Time-resolved Nad(p)h Fluorescencementioning
confidence: 84%
“…In these conditions, the cell is put in a fully oxidized state, with NADH dehydrogenated at maximum by flavoprotein complexes, leading to lower NAD(P)H fluorescence intensity. In this situation, fluorescence lifetime of the resolved component related to NAD(P)H in the ''bound'' state has been shown to be decreased, while that in the ''free'' state increased (Chorvatova et al, 2013b), resulting in prolonged mean lifetime. In this oxidizing condition, increase in the cell oxidation results in complete or partial depletion of oxidized nucleotides: fluorescence of NADH decreases, while that of FAD increases, leading to reduced NADH/FAD ratio.…”
Section: Cell Metabolic Signatures By Time-resolved Nad(p)h Fluorescencementioning
confidence: 97%
See 2 more Smart Citations
“…Over the past two decades the literature relating to°uorescence lifetime measurements of NADH, both in vitro and in vivo, has grown extensively, with many studies across di®erent cell lines and utilizing di®erent metabolic modulators establishing a link between changes in°u orescence lifetime and changes in cell metabolism. [8][9][10][11] Since aberrant metabolism is a hallmark of cancer, there has been considerable interest in exploiting measurements of cellular auto°uorescence lifetime to read out changes in metabolic state for the study, diagnosis and monitoring of cancer; such changes have been associated with a shift from oxidative phosphorylation to glycolysis. 12 Recently, the link between metabolic state and stem cell fate has o®ered an additional motivation for exploiting NADH lifetime-based readouts.…”
Section: Introductionmentioning
confidence: 99%